Étude de l’Électrosorption des cations prÉsents dans une solution polluée - BOURAHLA Sarra (My University, 2009)
The paramount objective of our work, within the framework of the environmental protection was devoted to the study of the process of electrosorption, for the elimination of cations. An experimental study concerning the techniques of adsorption and electrosorption of nickel and magnesium, by the activated granular carbon modified and as received was established to highlight the importance of certain experimental parameters in particular the time of contact, amount of coal, potential difference and pH in order to improve the capacity of elimination of nickel (II) and magnesium (II) by this activated carbons. The results obtained show an improvement of the capacity of adsorption of the various adsorbents studied compared to traditional adsorption particularly potential difference of 200 mV and 300 mV clean for each adsorbent.
Keywords: Electrosorption, adsorption, cations, activated granular carbon, potential difference.